Implementasi Sistem Informasi Manajemen pada Sistem Penjualan Makanan di Rumah Makan - Astri, Renita (Jurnal Ekonomi, 2013)
This study originated from the fact that the field is seen in many of the restaurants use in any manual system data processing sales. Payment system still use the food aid issue a cash register receipt sheet. Because the cash register is not designed to store transaction data, the total payment of the receipt note structure back to a book that will be reported to the leadership. This condition is of course still possible to condition the receiptstructure will be scattered or lost. The purpose of this research is to create a food menu Management Information System, the calculation of the total, as well as daily reports on the restaurant, which will then be implemented in order to achieve effectiveness and efficiency. The research was conducted by field research methode, research libraries, and research laboratories. Based on the research that has been done, it can be concluded that the design and implementation of management information systems can help home eating meals that will use this system to achieve effectiveness and efficiency, and through the tseting of these system, inormation system service in the home meal service can run smoothly anf very helpful the restaurant, particularly in calculating the total payments from customers and reporting to the leadership.